Pembinaan Keagamaan Mualaf di Pesantren Mualaf Indonesia Dompet Dhuafa - Dian Rosalina; Wasil Wasil (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2024)
This study examines the religious guidance of converts at Pesantren Mualaf Indonesia Dompet Dhuafa through the frameworks of Max Heirich’s conversion theory and Glock and Stark’s religiosity theory. Heirich’s theory is applied to analyze the transformation of spiritual identity and commitment among converts within the pesantren environment. Meanwhile, Glock and Stark’s theory is used to assess the dimensions of belief, practice, experience, and affective religiosity of the converts. The findings indicate that the pesantren's comprehensive approach and intensive support significantly enhance the religiosity and spiritual integration of the converts. This research provides valuable insights into the effectiveness of religious guidance methods in strengthening the religious identity and commitment of new Muslims in the pesantren context.